Reliability of ultrasound shear-wave elastography in assessing low back musculature elasticity in asymptomatic individuals. (April 2018) - Koppenhaver, Shane; Kniss, Joshua; Lilley, Daniel; Oates, Michael; Fernández-de-las-Peñas, Cesar; Maher, Ruth; Croy, Theodore; Shinohara, Minoru
Abstract: Patients with low back pain commonly exhibit impaired morphology and function of spinal musculature that may be quantifiable using shear-wave elastography (SWE). The purpose of this study was to assess the intra-rater and test-retest reliability of SWE elasticity measures of the lumbar erector spinae and multifidus muscles during rest and differing levels of contraction in asymptomatic individuals. This single-group repeated-measures design involved a baseline measurement session and a follow-up session 3 days later. The lumbar multifidus was imaged at rest and during three levels of contraction (minimal, moderate, and maximum). The lumbar erector spinae (illiocostalis and longissimus muscles) were imaged at rest only. Overall reliability estimates were fair to excellent with ICCs ranging from 0.44 to 0.92. Reliability was higher in the lumbar multifidus muscles than the erector spinae muscles, slightly higher during contraction than during rest, and substantially improved by using the mean of 3 measurements. By reliably quantifying impaired spinal musculature, SWE may facilitate an improved understanding of the etiology and treatment of low back pain and other muscle pain-related conditions such as trigger points and fibromyalgia.